COMPARISON OF INVESTMENT VALUE OF THE AFFECTED DEPARTURE TIME IN THE FIELD OF TRANSPORTATION TRAVEL BETWEEN THE CITY - BERNADI, ALEN (KURVA S JURNAL MAHASISWA, 2016)
Transport or transportation is a very important field of activity in the life of the Indonesian people . The importance of transport for the people of Indonesia are caused by several factors , among others , the geographical situation of Indonesia which consists of thousands of small and large islands , waters that comprise the bulk of the sea , rivers and lakes . As for the services of transportation services that we often encounter in their daily lives , namely motorcycles , cars , buses , and other service providers him. Another thing that is also important to the needs of transportation is a necessity , convenience , safety , and fluency of transportation. Mode of transportation is a term used to denote the means of transport used to move from one place to another . Moda normally used in transportation can be classified on the mode that runs on land , sailing on the sea and inland waters , as well as the mode of flying through the air.               Investment is a term with several meanings related to finance and economics. The term is associated with the accumulation of a form of assets with an expectation of profit in future. Sometimes, the investment is also known as capital investment. It is necessary for investment analysis of the transportation services travel between cities, in order to predict income and investment gains in the future. And can determine the ratio between the investment value of the time interval 1 hour / 15 minutes of departure to the time interval 1 hour / 30 minutes to departure whichever is more favorable between the interval time of 1 hour / 15 minutes of departure and the time interval 1 hour / 30 minutes of departure. From the research it was found that a more favorable time interval, ie the time interval with the departure 1 hour / 15 minutes. So interval 1 hour / 15 minutes to use the travel. The grounds are getting faster departing passengers, the more revenue or profits.               Performance transportation services company created to meet the needs of passengers who want public transportation between cities is convenient, safe , and fast . In accordance with the wishes of the whole society. Public transport is targeting all circles . With the price Rp.130.000 , - / Person .